Phenthoate 50% EC Compound Poisoning inducedIntermediate Syndrome–A Case Report - Shirol, Gulam Mohiyuddin Naeem; Mehta, Purvi (Indian Journal of Pharmacy Practice)
Poisoning by pesticides continues to be a serious global public health issue. More than 250,000 people die each year from pesticide poisoning, according to estimates from the World Health Organization. Nearly 900,000 people who commit suicide each year around the world are also represented by this figure in a sizeable proportion. Organophosphate insecticides are the most frequently responsible substances among the several pesticides that might cause mortality due to their high toxicity. Due to its frequent occurrence and likely outcome of respiratory failure, Intermediate Syndrome (IMS) is a significant contributor to organophosphate-related morbidity and mortality. IMS is managed appropriately on a supportive approach. Despite this, prompt establishment of ventilatory support, appropriate antidotal therapy, and early aggressive decontamination should all assist in reducing the severity and/or the occurrence of IMS. This is because in most cases, IMS is accompanied by severe organophosphate poisoning and ongoing acetylcholinesterase suppression.
Keywords: Phenthoate 50% EC; Compound poisoning; Intermediate syndrome; Organophosphate insecticide poisoning